Women's Economic Empowerment in the Informal Sector - Soputan, Grace Jenny; Kerebungu, Ferdinand (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2020)
Women's empowerment program in Indonesia has essentially been started since 1978. In its development, this effort has resulted in improvement in various ways. Some examples of the improvement are the improvement in conditions, degrees, and quality of life of women in various strategic sectors such as education, employment, economy, health, and family planning participation. Improvement in the empowerment process does not necessarily change the pattern of gender relations between men and women. To improve gender equality in the economy, women's economic actors need to be empowered. The purpose of this study is to examine the appropriate empowerment model for women in the informal sector. This is a case study involving observation, interviews, and Focus Group Discussion. The results of the study showed that women in the informal sector are not yet independent even though they have obtained facilitation from the government. The absence of government’s assistance in managing business resulted in the limited empowerment activities carried out by the government. This research offers a model of economic empowerment for women towards independence in economic activities.